STUDI EKSPERIMENTAL UAP KARBURATOR MENGGUNAKAN METODE KOMBINASI BUBBLING DAN METODE SPLASH DENGAN VARIASI BAHAN BAKAR PADA EMISI GAS BAKAR SEPEDA MOTOR SUPRA X - Dimas Adi Irawan; Ranto Ranto; Ngatou Rohman (Nozel : Jurnal Pendididikan Teknik Mesin, 2019)
The use of a steam carburetor is one way to reduce exhaust gas emissions where it works by mixing fuel and air in the room with an evaporation process so that the air and fuel mixture is more homogeneous. This study aims to see (1) the effect of using a steam carburetor on exhaust gases on a Supra X motorcycle; (2) the effect of using variations in exhaust gas emissions on the Supra X motorcycle; (3) the effect of using steam carburetors and fuel variations on the exhaust emissions of the Supra X motorbike. This research is a research, quantitative, descriptive, comparative, with experimental methods. The research used the 2x2 method which consists of independent variables using steam and conventional carburetors as well as variations of pertalite (RON 90) and pertamax (RON92) fuel. Exhaust gas emission testing is guided by the Indonesian National Standard (SNI) with three repetitions, for 20 seconds times the test The results of the study are as follows: First, the use of a steam carburetor produces lower exhaust emissions compared to conventional carburetors on a 100cc Supra X motorcycle. Second, pertalite fuel (RON 90) produces lower exhaust emissions compared to Pertamax fuel (RON 92). Third, the effect of using the type of carburetor and the type of fuel that produces the lowest exhaust emission, namely the steam carburetor using the combined splash and bubbling method with pertalite fuel with an average of 0.52% CO and 273.67ppm HC.